Fusobacterium nucleatum supresses anti-tumor immunity by activating CEACAM1. (3rd June 2019) - Gur, Chamutal; Maalouf, Naseem; Shhadeh, Amjad; Berhani, Orit; Singer, Bernhard B.; Bachrach, Gilad; Mandelboim, Ofer
ABSTRACT: Fusobacterium nucleatum (F. nucleatum ) is an oral anaerobe found to be enriched in colorectal cancer (CRC). Presence of F. nucleatum in CRC has been correlated with resistance to chemotherapy and poor prognosis. We previously demonstrated that the Fap2 outer-surface protein of F. nucleatum binds and activates the human inhibitory receptor TIGIT which is expressed by T and Natural Killer (NK) cells, and inhibits anti-tumor immunity. Here we show that F. nucleatum also binds and activates the human inhibitory receptor CEACAM1 leading to inhibition of T and NK cells activities. Our results suggest that using CEACAM1 and TIGIT inhibitors and specific targeting of fusobacteria should be considered for treating fusobacteria-colonized tumors